Desenvolvimento de um programa para análise não linear geométrica e física de treliças planas através da formulação co-rotacional - SILVA, Tiago Rodrigues da (Universidade Federal do Pará, 2017)
In this work, we carried out a study on the physical and geometrical non-linear structural analysis of plane trusses in co-rotational formulation. For the purposes of this analysis, it elaborated a computer system for teaching purposes. This paper presents the key simplifying assumptions of the problem and demonstrating all the equations governing the problem. To consider the nonlinear behavior of the material, constitutive equations of hyperelastic material were used, and the constitutive equations of Menegotto and Pinto model. Computational implementation phase we used the Matlab programming language, with general concepts of object-oriented programming. To validate the program, we compared the results obtained through this system to the available literature. In these validation tests and examples, it has proven efficacy and applicability of algorithms implemented in the analysis and its practicality in the use, it is possible to use the computer system for teaching and nonlinear analysis of plane trusses.